Northern Irish Poetry and Domestic Space - Hanna, Adam. author. aut Link
XXIV, 188 p.
Keywords: Northern Irish Poetry and Domestic Space explores why houses, in some ways the most private of spaces, have taken up such visibly public positions in the work of a range of prominent poets from Northern Ireland, examining the work of Seamus Heaney, Michael Longley, Derek Mahon and Medbh McGuckian.